(untitled) (Medical Forum Monthly, 2024)
Objective: Left atrial size and volume is significant clinical tool for testing diastolic function and chronicity of diastolic dysfunction by echocardiography. It involves measuring diameter in end systole internally and LA volume by prolate ellipse method. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Cardiology, Shaikh Zayed Hospital Lahore from July 2018 to December 2018. Materials and Methods: One hundred and forty seven renal failure patients from both genders within an age group of 15-75 years were undergone echocardiography. The related clinical history and findings were recorded. Results: There were 76 males and 71 females. The data analysis suggested that mean LA size was highest 38.35 in patients >50 years of age. Highest left ventricle ejection fraction (mean 69) and LV mass (mean 173) was presented in 31-40 years of age group. The greatest mean LA size (41.7±3.93) was noticed in severe graded patients. Conclusion: The LV measurements showed that 41-50 years of age was most vulnerable for abnormal echocardiographical findings and The LA measurement is the HbA1C% of diastolic dysfunction.